Secretory Carcinoma of the Parotid: Making the Correct Diagnosis of a Rare Salivary Gland Carcinoma When Molecular Biology Testing Is Not Available - Nelson Montalvo; David Galarza; Ligia Redrobán (Hindawi Limited, 2019)
Secretory carcinoma (SC) is a recently described entity occurring in the salivary glands. Before its description, SC was frequently classified as acinic cell carcinoma (ACC) or adenocarcinoma, not otherwise specified. Its particular histopathological and immunohistochemical characteristics are reminiscent of breast secretory carcinoma. Moreover, it displays a characteristic t(12;15) (p13;q25) translocation that results in the ETV6-NTRK3 gene fusion. This translocation has not been reported in any other salivary gland carcinoma. Identification of the t(12;15) (p13;q25) translocation is the gold standard for diagnosis, although some cases that do not present this specific translocation have already been reported. In such cases, diagnosis is challenging. In addition, some diagnostic pathology laboratories lack the resources to perform the molecular analysis to diagnose SC. In this scenario, morphology and immunohistochemistry are fundamental. Therefore, we report a case emphasizing the typical morphology of SC and its immunochemical profile to establish a final diagnosis without molecular biology tests. This case aims to demonstrate the importance of recognizing the typical presentation of a rare tumor so that clinicians will be informed or reminded of it and consider this entity among the differential diagnoses, when necessary. Moreover, in low-resource settings where molecular analysis is not available, being familiar enough with the histology of this tumor and using the immunoprofile as a key tool for differential diagnosis would be of great importance in establishing the correct diagnosis. The differential diagnosis includes, above all, acinic cell carcinoma and other salivary neoplasms such as intraductal carcinoma, low-grade mucoepidermoid carcinoma, and adenocarcinoma, not otherwise specified, which is actually a rule-out diagnosis.